2012
DOI: 10.1111/j.1750-3841.2012.02763.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities and Phenolic Compounds of Pigmented Rice Bran Extracts

Abstract: The present study revealed black and red rice bran shows high antioxidant activities and they contain high amount of phenolic compounds. Indeed, black and red rice bran could be better raw materials for manufacturing the food with high antioxidant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 24 publications
6
67
0
2
Order By: Relevance
“…Exogenous Spd may have stimulated the metabolic pathways leading to synthesis of certain groups of phenolic compounds responsible for the reducing ability in FRAP assays. This result confirmed earlier findings of greater antiradical ability in the red rice than in the black rice (Choi et al, 2007;Jun et al, 2012). Although the negative effects of salt stress on grain yield of rice have been widely reported, few studies have dealt with grain quality.…”
Section: Discussionsupporting
confidence: 82%
“…Exogenous Spd may have stimulated the metabolic pathways leading to synthesis of certain groups of phenolic compounds responsible for the reducing ability in FRAP assays. This result confirmed earlier findings of greater antiradical ability in the red rice than in the black rice (Choi et al, 2007;Jun et al, 2012). Although the negative effects of salt stress on grain yield of rice have been widely reported, few studies have dealt with grain quality.…”
Section: Discussionsupporting
confidence: 82%
“…Studies have proven that the active components of RB improve the human health because of the high content of antioxidants (Laokuldilok et al, 2011). Jun et al (2012) reported that black and red rice brans exhibited high content of phenolic compounds and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Rice bran has recently received considerable attention due to its beneficial health effects against diabetes, cancer and heart disease [3]. Its use as largely available and inexpensive source of natural antioxidants and bioactive peptides with health-promoting properties has been recently evaluated [10,11].…”
Section: Introductionmentioning
confidence: 99%